Supporting the medial hinge in proximal humerus fractures with an intramedullary plate. (June 2021) - Gardenbroek, Tjibbe J.; Oud, Sharon; Formijne Jonkers, Henk A.; Goslings, J. Carel
Abstract: Proximal humerus fractures are common and approximately 20% of displaced fractures may benefit from surgery. A lack of medial support is found to be a predictor of failure after surgical fixation of proximal humerus fractures. The optimal technique for restoring the medial hinge is unclear. We describe two cases of patients with a dislocated 4-part humerus fracture treated with a locking plate and an additional small intramedullary plate to support the medial hinge. This technique is simple and allows for an enhanced stability of the medial hinge during and after surgery.